2021
DOI: 10.1099/jmm.0.001236
|View full text |Cite
|
Sign up to set email alerts
|

Implication of efflux pumps and ERG11 genes in resistance of clinical Trichosporon asahii isolates to fluconazole

Abstract: Introduction. Trichosporon asahii has been recognized as an opportunistic agent having a limited sensitivity to antifungal treatment. Hypothesis/Gap Statement. Molecular mechanisms of azole resistance have been rarely reported for Trichosproron asahii. Similar to other fungi, we hypothesized that both ERG11 gene mutation and efflux pumps genes hyper-expression were implicated. Aim. The current work aimed to study the sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“… Sasani et al (2021) reported that the formation of biofilms and the overexpression of ERG11 and UPC2 genes in Candida tropicalis were related with fluconazole resistance. Abbes et al (2021) found that Mdr gene overexpression in Trichosporon asahii isolates was significantly associated with fluconazole resistance. However, there are no articles reporting why fluconazole resistance is high also in this complex.…”
Section: Discussionmentioning
confidence: 99%
“… Sasani et al (2021) reported that the formation of biofilms and the overexpression of ERG11 and UPC2 genes in Candida tropicalis were related with fluconazole resistance. Abbes et al (2021) found that Mdr gene overexpression in Trichosporon asahii isolates was significantly associated with fluconazole resistance. However, there are no articles reporting why fluconazole resistance is high also in this complex.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown a reduction in the susceptibility of fungi compared to the available classes [ 23 , 24 ]. The main factors related to decreased antifungal susceptibility are drug target overexpression, efflux pumps, and amino acid substitution [ 25 , 26 ]. In addition, another limitation to the use of current antifungals is the presence of adverse effects, the main ones being nephrotoxicity and hepatotoxicity [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tendo em vista a gravidade das infecções sistêmicas e a crescente resistência aos antimicrobianos atualmente utilizados na clínica, é preciso uma constante atualização acerca da patogenia da doença e da interação entre o fungo e o bem como o correto diagnóstico, considerando os fatores de virulência e seus potenciais alvos farmacológicos (DUARTE-OLIVEIRA et al, 2017;ABBES et al, 2021;MEHTA et al, 2021).…”
Section: Introductionunclassified